Cellu(h)er Resistance: The Body with/out Organs? - Patterson, Pam (InTensions, 2009)
The Body without Organs is a pure living body. It is the field in which intensity plays. As an abstraction, whose essence varies from person to person or from moment to moment, it is manufactured. As an abstraction, it also needs to be defined and then something must happen on it, not like on a canvas but rather like on a matrix. It gains reality in proportion to the intensity which plays upon it. Gilles Deleuze & Félix Guattari Cellu(h)er Resistance: The Body with/out Organs? is a performance/installation that acknowledges the use of theoretical and artistic practices for re-viewing the body-as-matrix. In this work, I reconfigure the (my) female body, marked by the effects of aging, medical interventions and cancer, in public space exploring the challenges and rewards of negotiating the body-as-terrain as a person with a disability and cancer. A feminist investigation and reconstruction of my "matrix" has involved years of excavating my whiteness, my privilege, my ability. As I re-entered the field for this work, following years of disease and illness, the pain of poverty, dis-ability and with a reconfigured surgical body, I shifted my understandings. As multi-disciplinary performance/installation artist, I incorporate, in my practice, performance, drawing, text/theory and photo-derived imagery in various configurations. The detritus I use here as content - the amputated breast, the crippled legs, the swollen, distorted hands, the bags, the sags, the corpulent middle - marks the impact that life has had on my body and art. As a person living with a disability, and in a body altered by breast cancer surgery, I engage with issues around in/visibility, with the body-grotesque as site/sight - and with pain. It isn’t the case that s/he likes pain per se; rather, s/he likes being a Body without Organs, and the pain is the price s/he’s willing to pay for that. I energize this content and these issues through a performative/visual praxis. My intention is to conceive of what “life in the face of death” means, and apprehend my own identity, in anxious and immediate (un)certainty in time and space. Repeatedly, I experience my efforts to capture my experiences as/in art as but moment-by-moment wrestling matches with the angel of death. My focus has been not to normalize this struggle, but rather to engage with it as a complex visually and performatively rich intra- and inter-cultural autobiographical site and to see if such engagement might bring me and others closer to understanding life in/and culture(s). Sé do bheatha a bhean ba léanmhar. (Welcome oh woman who was so afflicted). Inspired by my daughter and her rediscovery of her Irish heritage and language, I speak in this work, as well, through the figure of 16th century female Irish sea captain Granuaille. Using these and other elements - red “blood”, dirt, paper - to propel my passion, I ritually reconfigure another body for my body. As it is performative, it is (un)accomplished the moment I undertake it. There are sounds, images, becomings. The images - clouded sunsets, my daughter and her horse poised to leap, drawings of a breast, a bowl, a black and white projected film of my younger intact torso, and scattered wall text - remain as traces playing over the gallery walls, as if mis/displaced. As a completed work, Cellu(h)er Resistance: The Body with/out Organs? ironically gains reality as it moves closer to be-coming dis/embodied. In the night a child is screaming. Cancer is in my head for life. What path am I being asked to step away from on behalf of my life? Crossing cancer’s space - it’s a different time zone a different space; a long breathing space in which the mind gathers its strength & takes stock of its courage. Listen, I have not lost my power. I have not forgotten who I am. Once my gods were intimates. Once I made gestures of pure exuberance. Now, my hands invent another body for my body. As the world reduces to a small brilliant space where every thought and movement is vital to my salvation, let me suddenly have a center. Let me leave a silhouette on the world. Let me stand composed before a million universes.(all excerpts from Cellu(h)er Resistance: The Body with/out Organs?)